2007
DOI: 10.1111/j.1365-2427.2007.01888.x
|View full text |Cite
|
Sign up to set email alerts
|

The significance of side‐arm connectivity for carbon dynamics of the River Danube, Austria

Abstract: 1. Side-arms connected to the main stem of the river are key areas for biogeochemical cycling in fluvial landscapes, exhibiting high rates of carbon processing. 2. This work focused on quantifying autochthonous and allochthonous carbon pools and, thereby, on comparing transport and transformation processes in a restored side-arm system of the River Danube (Regelsbrunn). We established a carbon budget and quantified carbon processing from March to September 2003. In addition, data from previous studies during 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
44
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(46 citation statements)
references
References 49 publications
2
44
0
Order By: Relevance
“…A similar trend in higher denitrification rates has also been documented for wetlands connected to the Po River (Racchetti et al, 2010). Higher denitrification rates (94 mg N m −2 h −1 , ca.…”
Section: Importance Of Connected Floodplainssupporting
confidence: 79%
See 2 more Smart Citations
“…A similar trend in higher denitrification rates has also been documented for wetlands connected to the Po River (Racchetti et al, 2010). Higher denitrification rates (94 mg N m −2 h −1 , ca.…”
Section: Importance Of Connected Floodplainssupporting
confidence: 79%
“…In this study, the restored site experienced an increase in denitrification rates compared to the disconnected site, suggesting that increasing the continuous and long-lasting surface water connection periods will increase the overall denitrification rate as well as its efficiency (Kjellin et al, 2007;Klocker et al, 2009;Racchetti et al, 2010). Yet, as shown in Experiment 1, increasing nitrate concentration does not lead to higher denitrification rates in short time.…”
Section: Importance Of Restorationmentioning
confidence: 54%
See 1 more Smart Citation
“…Focussing on organic carbon (TOC) and nitrogen (TN), deposition during overbank floods is an important ecosystem function which provides important benefits as water quality enhancement or mitigation of greenhouse effect (Johnston, 1991;Day et al, 2004;Verhoeven et al, 2006, IPCC, 2007. At the reach scale, TOC and TN exchange between the main channel and its adjacent floodplain plays a key role in the ecological functioning (Junk, 1999;Robertson et al, 1999;Tockner et al, 1999;Tockner at al., 2000;Thoms, 2003;Knosche, 2006;Preiner et al, 2008). Previous research has shown how human-induced changes at the basin and reach scale have decreased the potential of riverine floodplains to act as sediment-associated nutrient sinks (Noe and Hupp, 2005;Owens et al, 2005;Pierce and King, 2008;Cabezas et al, 2009;Cabezas and Comin, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Reaeration is strongly influenced by turbulent mixing [37], and because of the low velocities in a stream with a relatively moderate cross sectional area (approximately 3.5 m in width by 0.5 m in depth), we assumed the reaeration coefficient to be zero, i.e., disregarding stream reaeration caused by water movement. We acknowledge that neglecting the coefficient may result in lower estimation of metabolic rates, as some studies have shown that CO 2 exchange occurs between the atmosphere and still water in lakes [38] and river backwater [39]. The primary purpose of our study is to investigate potential harvest effect on stream metabolism, rather than give a precise quantification of metabolic rates.…”
Section: Metabolic Calculationsmentioning
confidence: 99%